PELATIHAN PEMANFAATAN APLIKASI ANDROID UNTUK PENINGKATAN BERBAHASA INGGRIS: Training on the Use of Android Applications to Improve English Skill - Sasa Ani Arnomo; Jazuli Jazuli (PUAN INDONESIA, 2023)
Hearing the word smartphone technology may not seem foreign to some people, on the other hand, for certain people something is rarely used by the technology in it. The application in this smartphone itself is an existing facility on Android that allows users to be able to use it. Among the applications that can improve English skills are Hangman Game, Simon Says and Word Match. There are several games that can later be loaded to increase the user's skills. Given the importance and good use value of smartphone technology, it is necessary to introduce it to the community through community service programs, in this case the community that is deemed necessary at this time is the law office of Agus-Rio & Partners. Jl. Trans Barelang, Taman Cipta Asri II Block Boulevard A-12 with the target of participants being employees and the Taman Asri housing community. It is also undeniable that the use of smartphone technology is important. Where Law and Human Rights Offices are not only related to assistance within the country but also sometimes receive legal aid services outside the country such as Singapore and Malaysia. As is well known, certain activities at the Law Office require the presence of many participants, including employees and cooperating parties. It is hoped that through training on the use of smartphone technology this can become a platform for the basis for honing their English language skills.